Whey-Based Protein Powder Supplement - Andino, Edwin Fabián Cerda; Ochoa, Zoila Eliana Zambrano; Palma, Gabriela Beatriz Arias (Journal of Posthumanism, 2025)
This research was carried out to take advantage of the whey from cheese production in our country, which, for many years, was considered waste and generated a negative environmental impact on our environment. Currently, the industry has focused on giving this byproduct a new opportunity. This work seeks to develop a protein supplement in powder from whey concentrate to complement the nutritional and protein needs of people, and also contribute to sustainable practices within the food industry. Ultrafiltration and spray drying techniques were used to prepare the concentrate, and maltodextrin, organic cocoa powder, and a mixture of stabilizers were added to prepare the protein supplement, to give added value to the product. This research work included a test series, which resulted in a protein content of 30.18% in the best treatment, the microbiological tests performed on this treatment comply with the requirement from INEN 2983 standard for nutritional supplements, while the results obtained through sensory analysis highlight the acceptability of treatment 1, which contains a 29.48% protein. All the treatments analyzed in this research provide more than 20% of the daily protein requirement, being considered a high protein product according to the INEN 1334:3 standard, and it has exceptional nutritional properties and attractive sensory characteristics.